Potential therapeutic role of SIRT1 in age- related hearing loss - Zhao, Tingting; Tian, Guangyong (Frontiers in Molecular Neuroscience, 2022)
Age-related hearing loss (ARHL) is a major public health burden worldwide that profoundly affects the daily life of elderly people. Silent information regulator 1 (SIRT1 or Sirtuin1), known as a regulator of the cell cycle, the balance of oxidation/antioxidant and mitochondrial function, has been proven to have anti-aging and life-extending effects, and its possible connection with ARHL has received increasing attention in recent years. This paper provides an overview of research on the connection between SIRT1 and age-related hearing loss. Topics cover both the functions of SIRT1 and its important role in ARHL. This review concludes with a look at possible research directions for ARHL in the future.